Coupled domain wall oscillations in magnetic cylindrical nanowires - Murapaka, Chandrasekhar (2015)
We report on transverse domain wall (DW) dynamics in two closely spaced cylindrical nanowires. The magnetostatically coupled DWs are shown to undergo an intrinsic oscillatory motion along the nanowire length in addition to their default rotational motion. In the absence of external forces, the amplitude of the DW oscillation is governed by the change in the frequency of the DW rotation. It is possible to sustain the DW oscillations by applying spin-polarized current to the nanowires to balance the repulsive magnetostatic coupling. The current density required to sustain the DW oscillation is found to be in the order of 105 A/cm2. Morover, our analysis of the oscillation reveals that the DWs in cylindrical nanowires possess a finite mass.